A Gender-Based Study of Sensation Seeking in Patients with Coronary Artery Disease Compared with Healthy Subjects - Ezzati, Davoud; Hashemi Nosrat Abad, Touraj; Babapour Kheiroddin, Jalil; Namdar, Hossein; Taban Sadeghi, Mohammadreza; Hakimi, Masoumeh; Sadeghi, Babak; Samani, Zhila (International Journal of Cardiovascular Practice, 2018)
Introduction: The relationship between psychological factors and Coronary Artery Disease (CAD) is one of the topics that has occupied the minds of researchers in the field of health psychology. The present research aimed at studying the levels of sensation seeking in coronary patients and healthy subjects.Methods: Two hundred and twenty-three coronary patients and 255 healthy subjects completed the Sensation Seeking Scale-form V (SSS?V). Next, 100 coronary cases (50 males and 50 females) that had referred to Madani Heart Hospital, Tabriz, Iran, and 100 healthy subjects, were compared in terms of levels of sensation-seeking. All participants were selected by purposeful sampling (aged 25 to 64 years). Data were analyzed by Multivariate Analysis of Variance (MANOVA) through the SPSS 18 software.Results: Coronary male patients scored higher than coronary female patients in thrill and adventure seeking and healthy males scored higher than healthy females in boredom susceptibility. Healthy females scored higher than coronary females in thrill and adventure seeking, and in boredom susceptibility subscale, healthy males scored higher than coronary males.Conclusions: The identification of individuals with sensation seeking features will allow the identification of susceptible coronary patients for preventive procedures.